Rosja i Rosjanie w wierszach Mazurów - Chojnowski, Zbigniew (Acta Polono-Ruthenica, 2006)
XIX century Mazurian’s poetry likewise their poetry from the beginning of the XX century enclose motives ant themes connected with Russians and the Russian Empire. The Russian Empire itself and Russian as the nation were perceived by Mazury inhabitants throughout military and political primacy in the region. That attitude grows to the myths that had been formed by thepropaganda of Prussia Empire.Mazurian poetry supplied documentary evidence of the supremacy of Russian Empire in Eastern Prussia due to military conflicts (ex. „The Seven-Years War”, the Napoleonic wars, and also the I World War).Mazurian in their poetry established not only the stereotype of Russian and the Russia Empire as the aggressor but also their trepidation and deference in the same time were shown yet.